2014
DOI: 10.1016/j.sbspro.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse Use in Thesis Abstracts: A Cross-cultural Study

Abstract: The present study aims to investigate cultural variations in the use of metadiscourse between Turkish and USA postgraduate students' abstracts in MA thesis written in English. The taxonomy was borrowed from Hyland (2005). The corpora in the present study comprise a total of 52 thesis abstracts written in English from the department of English Language Teaching, 26 thesis from USA students and 26 from Turkish students. Both qualitative and quantitative methods were employed to analyse the texts in the corpora. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 10 publications
7
52
0
Order By: Relevance
“…Rezaei et al (2015) investigated MD in a corpus of 30 MA theses and revealed that boosters had the highest percentage with 46.68 and with 3 % of MD markers, hedges were among the least frequent items. In another study conducted by Özdemir and Longo (2014), boosters were observed 2.8 times per 10.000 words in the master's theses of Turkish students while it was employed 73.2 times in the master's theses of American students. There was a striking difference in the use of boosters in their study.…”
Section: Extracted From Ctaementioning
confidence: 95%
See 2 more Smart Citations
“…Rezaei et al (2015) investigated MD in a corpus of 30 MA theses and revealed that boosters had the highest percentage with 46.68 and with 3 % of MD markers, hedges were among the least frequent items. In another study conducted by Özdemir and Longo (2014), boosters were observed 2.8 times per 10.000 words in the master's theses of Turkish students while it was employed 73.2 times in the master's theses of American students. There was a striking difference in the use of boosters in their study.…”
Section: Extracted From Ctaementioning
confidence: 95%
“…Many scholar have argued that the use of MD varies across cultures. Özdemir and Longo (2014) compared the use of metadiscourse between Turkish and USA postgraduate students' in abstracts in MA thesis written in English by using the taxonomy of Hyland. The analysis confirmed that there were some cultural differences in the amounts and types of metadiscourse.…”
Section: Volume 6 Issue 1 March 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…To be more specific, there are few studies investigating stance employed in dissertations written by EFL students, especially, Thai doctoral students. To the best of my knowledge, only five studies (Ahmad & Mehrjooseresht, 2012;Gil-Salom & Soler-Monreal's, 2014;Hyland, 2005;Ozdemir & Longo, 2014;Rahimivand & Kuhi, 2014) were conducted to investigate authorial stance of EFL graduate dissertations. To this end, I intend to conduct a corpus-based study to explore the use of authorial stance in the Introduction and Discussion sections of the dissertations since the PhD dissertations are important pieces of papers-gateway to academic achievement, the researchers must not only process evaluative thinking but creditably express their own evaluations to show their standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…With the interactional metadiscourse markers in English, It doubts whether there may be losses in both semantically and functionally in the process of translating Turkish to English. Ozdemir and Longo (2014) investigate cultural variations in the use of metadiscourse between Turkish and USA postgraduate students' abstracts in MA thesis written in English. The study also compares the incidence of both interactive and interactional metadiscourse markers between 26 theses of USA students and 26 of Turikish students.…”
Section: The Previous Studies Of the Rhetorical Use Of Metadiscoursementioning
confidence: 99%